NUTRITIONAL EDUCATION AND ASSESSMENT OF SCHOOLCHILDREN: EXTENSION EXPERIENCE REPORT IN A PUBLIC SCHOOL IN EUNÁPOLIS, BRAZIL - Almeida da Silva, Flaelma; de Lima, Diana; Santos Rocha Novais, Elines; Clara Sousa Martins, Ana (Health and Society, 2025)
This article presents a report of an extension activity of qualitative, descriptive, and participatory nature, carried out with 4th-grade elementary school students at a public school in Eunápolis, Bahia. The general objective was to promote awareness about healthy eating in the school environment and to observe, in a descriptive manner, the eating habits and nutritional status of the participating children. The choice of the theme is justified by the importance of health promotion and food education in school settings, especially in socially vulnerable contexts where inadequate dietary practices and cases of malnutrition are still frequent. Activities included food-based dynamics, BMI calculation, discussion circles, nutritional guidance, and an educational lecture with the school cafeteria staff. The descriptive survey indicated that most children consume processed foods daily, with a predominance of cases of thinness. The experience demonstrated the pedagogical potential of playful and educational interventions in shaping healthy eating habits in the school context.